PRESERVATION BUGIS AND MADURA LANGUAGE IN THE DOMINATION JAVANESE IN THE KEMUJAN, KARIMUNJAWA - Nurkhikmah, Tati (PEOPLE: International Journal of Social Sciences, 2015)
Mother tongue is the first language that is learned by language speakers. UNESCO captures the concerns to the world that continue to lose their mother tongues. UNESCO estimates that approximately 3,000 languages will extinct by the end of this century. In the midst of these concerns there are still some tribes in Indonesia who still retain their mother tongue, among others, the Bugs and Madura tribe in the village of Kemujan, Karimunjawa. Both tribes have their own reasons and ways to maintain their native language. The purpose of this study is to find out why and how the preservation of Bugs and Madura language are. The method used is descriptive qualitative method. Stages in the method include the preparation, dissemination of research instruments, data collection, data analysis, and reporting. Meanwhile, the data collection techniques used is interview and the distribution of questionnaires. The results of the study are in the form of reason and manner of Bugs and Madura tribe in maintaining their language. The language used is preserved due to several reasons, including Bugs and Madura society appreciates language brought by the ancestors, wants to show identification, communication needs, economic needs, and feel they have their own native language. Some of these reasons applied in two ways, namely retention in the family environment and preservation in the community. The research results can be used as a reference for mother tongues in Indonesia and other country which have extinct mother tongues. So with those preservation efforts of the mother tongues can be preserved well.